Comparison Of The Powers Of Energy Losses In A Variable Capacity Displacement Pump Determined Without Or With Taking Into Account The Power Of Hydraulic Oil Compression - Paszota Zygmunt (Polish Maritime Research, 2015)
Powers of energy losses in a variable capacity displacement pump are compared with or without taking into account the power of hydraulic oil compression. Evaluation of power of liquid compression in the pump was made possible by the use of method, proposed by the Author, of determining the degree of liquid aeration in the pump. In the method of determining the liquid aeration in the pump and of powers of volumetric losses of liquid compression a simplified formula (qPvc × ΔpPi)/2 was used describing the field of indicated work of volumetric losses qPvc of liquid compression during one shaft revolution at indicated increase ΔpPi of pressure in the chambers. Three methods were used for comparing the sum of powers of volumetric losses ΔPPvl due to leakage and ΔPPvc of compression and also ΔPPm|ΔpPi of mechanical losses resulting from increase ΔpPi of indicated pressure in the working chambers.